what do you need done with this question. like do you need it simplified or facotr by grouping what i need more info
Answer:
- (fog)(3) = f(g(3)) = f(12) = 60
Step-by-step explanation:
Given
Finding (fog)(x)
(fog)(x) = f(g(x))
(fog)(x) = f(x+9)
(fog)(x) = 5(x+9) ∵ substitute x as x+9 in the f(x)
(fog)(x) = 5x+45
Finding (gof)(x)
(gof)(x) = g(f(x))
(gof)(x) = g(5x)
(gof)(x) = 5x+9 ∵ substitute x as 5x in the g(x)
Finding (fog)(3)
(fog)(3) = f(g(3))
substitute x = 3 in the g(x)=x+9
g(x) = x+9
g(3) = 3+9
g(3) = 12
so
(fog)(3) = f(g(3)) = f(12)
now substitute x = 12 in f(x) = 5x
f(x) = 5x
f(12) = 5(12)
f(12) = 60
Thus,
(fog)(3) = f(g(3)) = f(12) = 60
Answer:
one half×k + 5 is the correct expression that represents Jonah's salary
Answer:
8x^2-2x+8
Step-by-step explanation:
(2x^2−3x+9)+(6x^2+x−1)
Combine like terms
2x^2 +6x^2 -3x+x +9 -1
8x^2-2x+8
A=48
b=144
c=-84
First, you simplify the second equation by multiplying 6 to 2x and 6 to 7. Then, you get the two equations, (4x-2) times (12x+42). You then use the FOIL method, multiplying 4x to 12x, 4x to 42, -2 to 12x, then -2 to 42. Simplify. Then number before x squared is your a value, value before x is b, and the value without x is c.